The tributary relations between China’s Song Dynasty and Vietnam’s Dinh, Le and Ly Dynasties: Effects on their political sustainability - Ku, Boon Dar (Universiti Malaya, 2019)
This article reviews the history of China-Vietnam’s relations from the time of the independence of Vietnam in 939 until the reign of the Ly dynasty (1010 – 1225). It focuses on how China and Vietnam established a relationship based on the tributary system and how far these early ties had affected the political continuity of the Chinese Song and the Vietnamese Dinh, Le and Ly dynasties. In addition, this is an attempt to analyse Vietnam’s view on China’s World Order in its relationship with China. It also illustrates that China’s “all under heaven” concept suggests a sense of unity in the Chinese world, derived from the moral conformity of its society; and how during the Song dynasty, China based itself on this moral conformity when it set out to develop a relationship with its neighbours, in this case, Vietnam.